PREVALENCE OF PHYSICAL DEVELOPMENT OF PUPILS OF THE KRASNODAR TERRITORY - E. I. Kondratieva; S. V. Mozgonova; D. V. Sutovskya; B. I. Zobenko; E. I. Kleshenko; L. L. Sedyeva (Кубанский научный медицинский вестник)
Students surveyed in 1927 Krasnodar territory aged 7–17 years. It is shown that a body mass index of the Krasnodar territory students mostly average – 43,6%. Percentile ranks are designed to assess the physical development of children 7–17 years for growth, weight and BMI adjusted for age and sex. A comparison of the studied parameters with physical development, WHO 2007. In general, children with high rates prevail over children with low height and weight. Body weight above 95 centile was noted in 11,2%, less than 5 centile – 2,8% of the school, which is 4 times less. Tall (over 95 centile) – 7,1% versus 2,7% growth – less than 5 centile.